Data from Public Agencies - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Language data in the form of translation memory, parallel texts and term resources, from different organisations, most of them public agencies.

Purpose:

Language data in the form of translation memory, parallel texts and term resources, from different organisations, most of them public agencies.

Språkdata i form av översättningsminnen, parallella texter och termresurser från olika organisationer, de flesta myndigheter.

Syfte:

Språkdata i form av översättningsminnen, parallella texter och termresurser från olika organisationer, de flesta myndigheter.
Myndighetsdata
Keywords: PUBLIC ADMINISTRATION; OFFENTLIG FÖRVALTNING; Social Sciences; Samhällsvetenskap; Languages and Literature; Språk och litteratur; Public Administration Studies; Studier av offentlig förvaltning